PROFILE THE LIFESTYLE OF OLDER GROUP OF PARTICIPANTS IN A GYM PRIVATE INSTITUTION OF PORTO ALEGRE (Fiep Bulletin - online, 2014)
The global aging has increased considerably in recent years, but the quality of life of envelhecentes has been influenced by several factors, the main one being the lifestyle. The aim of this study was to analyze the lifestyle of the elderly participants in a group exercise. The sample consisted of 41 patients of both sexes, aged 60 years. The survey instrument used was the pentacle of Welfare, through the questionnaire Profile Individual Lifestyle (NAHAS 2001, p. 21). The lifestyle adopted by this group of seniors were considered satisfactory among the five components of the lifestyle analyzed. The results suggest that older adults who perform physical activities regularly seek to adopt a healthier lifestyle, and this has increased the life expectancy of this population.